Home environment and social skills of Japanese preschool children pre- and post-COVID-19. Issue 15 (18th November 2022) - Li, Xiang; Jiao, Dandan; Matsumoto, Munenori; Zhu, Yantong; Zhang, Jinrui; Zhu, Zhu; Liu, Yang; Cui, Mingyu; Wang, Yanlin; Qian, Meiling; Ajmal, Ammara; Afsari Banu, Alpona; et al.
ABSTRACT: The COVID-19 pandemic has impacted the daily life and social relationships of pre-school children globally. While many studies have examined the impact of the pandemic on children, few have compared the home environment and children's social skills before and after the pandemic. To address this research gap, we used data from the Japan Child Care Cohort study, which included questions on home environment answered by parents (1748 in 2019 and 1349 in 2020) of children aged 0–6 years using self-reported questionnaires and data on the social skills of children aged 1–6 years (1917 in 2019 and 1989 in 2020) that were evaluated by childcare professionals in childcare centres. Using the Chi-square test, home environments and social skills were compared. We found that frequencies of family meals, no punishment, and a positive attitude toward children's mistakes were higher in 2020. In contrast, frequencies of shopping together, visiting children's friends and relatives, and having social support from others were lower in 2020. Additionally, children's social skills in 2019 were better than in 2020. Childcare institutions can consider these differences and create a support plan to ensure quality child-rearing practices and healthy child development.